Directional R-Loop Formation by the CRISPR-Cas Surveillance Complex Cascade Provides Efficient Off-Target Site Rejection - Marius Rutkauskas; Tomas Sinkunas; Inga Songailiene; Maria S. Tikhomirova; Virginijus Siksnys; Ralf Seidel (Cell Reports, 2015)
CRISPR-Cas systems provide bacteria and archaea with adaptive immunity against foreign nucleic acids. In type I CRISPR-Cas systems, invading DNA is detected by a large ribonucleoprotein surveillance complex called Cascade. The crRNA component of Cascade is used to recognize target sites in foreign DNA (protospacers) by formation of an R-loop driven by base-pairing complementarity. Using single-molecule supercoiling experiments with near base-pair resolution, we probe here the mechanism of R-loop formation and detect short-lived R-loop intermediates on off-target sites bearing single mismatches. We show that R-loops propagate directionally starting from the protospacer-adjacent motif (PAM). Upon reaching a mismatch, R-loop propagation stalls and collapses in a length-dependent manner. This unambiguously demonstrates that directional zipping of the R-loop accomplishes efficient target recognition by rapidly rejecting binding to off-target sites with PAM-proximal mutations. R-loops that reach the protospacer end become locked to license DNA degradation by the auxiliary Cas3 nuclease/helicase without further target verification.